European Carbon Dioxide Removal Policy: Current Status and Future Opportunities - Tamme, Eve; Beck, Larissa Lee (Frontiers in Climate, 2021)
Over the past two years, the European Union, Norway, Iceland, and the UK have increased climate ambition and aggressively pushed forward an agenda to pursue climate neutrality or net-zero emissions by mid-century. This increased ambition, partly the result of the Intergovernmental Panel on Climate Change's landmark findings on limiting global warming to 1.5°C, has also led to a renewed approach to and revitalized debate about the role of carbon capture and storage and carbon dioxide removal. With increasing climate ambition, including a proposed mid-century climate neutrality goal for the whole European Union rather than requiring each country to achieve climate neutrality on their own, the potential role of technological carbon removal is emerging as one of the critical points of debate among NGOs, policymakers, and the private sector. Policymakers are starting to discuss how to incentivize a carbon removal scale-up and whether or how to integrate it into existing sectoral policies, including the European Union Emissions Trading System. What encompasses the current debate, and how does it relate to carbon removal technologies' expected role in reaching climate neutrality? This perspective will highlight the arguments for near-term development of a comprehensive carbon removal policy framework. It will also shine a light on the current status of negative emission technologies and the role of carbon capture and storage in delivering negative emissions in Europe's decarbonized future. It will also analyze the role of carbon markets, including voluntary markets, as potential incentives while exploring policy pathways for a near-term scale-up.